STRATEGY IN APPLYING LOVE LANGUAGE TO ENHANCE THE QUALITY OF RELATIONSHIP IN CAREER FAMILY - Fajriantini, Yaumul Sabrina; Wafiroh, Ani; Fiqqih Alfathoni, Ahmad (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
Love language is a trendy term these days. However, the application of love language is largely ignored by society, especially career families. For this reason, this study aims to describe how career families apply love language strategies in improving the quality of their relationships and how it impacts their family harmony. A qualitative research method was used to collected a phenomenological approach. Data collection techniques were used through in-depth interviews and observations of career families. The results of this study are career families who apply the concept of love language in their families will make it easier for them to improve the quality of family relationships where there are many demands by career families both at work and very little time with family. Therefore, love language is very necessary in career families. In addition, there are impacts if career families do not apply love language in their families, so that small conflicts arise in the household, such as infidelity, differences of opinion, and damage to the relationship between children and parents.